2010
DOI: 10.4310/jdg/1271271795
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar solutions and translating solitons for Lagrangian mean curvature flow

Abstract: Abstract. We construct many self-similar and translating solitons for Lagrangian mean curvature flow, including self-expanders and translating solitons with arbitrarily small oscillation on the Lagrangian angle. Our translating solitons play the same role as cigar solitons in Ricci flow, and are important in studying the regularity of Lagrangian mean curvature flow.Given two transverse Lagrangian planes R n in C n with sum of characteristic angles less than π, we show there exists a Lagrangian selfexpander asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 24 publications
2
81
0
Order By: Relevance
“…The symplectic mean curvature flow was studied in [2-4, 10, 11, 22]. There are many references for Lagrangian mean curvature flows (see [8,[16][17][18][19][20][21]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symplectic mean curvature flow was studied in [2-4, 10, 11, 22]. There are many references for Lagrangian mean curvature flows (see [8,[16][17][18][19][20][21]). …”
Section: Introductionmentioning
confidence: 99%
“…Symplectic or Lagrangian translating solitons were studied in [11,12,16,18] recently. In [11,12,18], some kinds of Liouville theorems were proved, and in [16], the authors constructed Lagrangian translating solitons.…”
Section: Introductionmentioning
confidence: 99%
“…Note, that it was shown by Joyce, Lee and Tsui in [4] that for any ǫ ∈ (0, 1) there exist non trivial translating Lagrangian solitons which satisfy cos α ≥ ǫ.…”
Section: Introductionmentioning
confidence: 99%
“…Colding and Minicozzi [11] showed that the only stable selfshrinkers of the MCF for initial smooth closed embedded surfaces in R 3 are cylinders and spheres. For the Lagrangian MCF, Joyce et al [23], Anciaux [3] and Wang [29] have examples. There are other results in different contexts.…”
Section: Introductionmentioning
confidence: 99%